A divergent Anaplasma phagocytophilum variant in an Ixodes tick from a migratory bird; Mediterranean basin. Issue 1 (1st January 2020) - Hoffman, Tove; Wilhelmsson, Peter; Barboutis, Christos; Fransson, Thord; Jaenson, Thomas G.T.; Lindgren, Per-Eric; Von Loewenich, Friederike D.; Lundkvist, Åke; Olsen, Björn; Salaneck, Erik
ABSTRACT: Anaplasma phagocytophilum (AP) has vast geographical and host ranges and causes disease in humans and domesticated animals. We investigated the role of northward migratory birds in the dispersal of tick-borne AP in the African-Western Palearctic. Ticks were collected from northward migratory birds trapped during spring migration of 2010 at two localities in the central Mediterranean Sea. AP DNA was detected by PCR ( gltA and 16S rRNA) and variant determination was performed using ankA sequences. In total, 358 ticks were collected. One of 19 ticks determined as Ixodes was confirmed positive for AP DNA. The tick was collected from a woodchat shrike ( Lanius senator senator ) trapped in Greece, and molecularly determined to belong to the I. ricinus complex and sharing highest (95%) 16S RNA sequence identity to I. gibbosus . The ankA AP sequence exhibited highest similarity to sequences from rodents and shrews (82%) and ruminants (80%). Phylogenetic analyses placed it convincingly outside other clades, suggesting that it represents a novel AP variant. The divergent Ixodes species harboring a novel AP variant could either indicate an enzootic cycle involving co-evolution with birds, or dissemination from other regions by avian migration. None of the 331 Hyalomma marginatum sensu lato ticks, all immature stages, were positive for AP DNA, lending no evidence for the involvement of Hyalomma ticks transported by birds in the ecology of AP.